The Examination of Information Sharing Levels of Academicians Working in the Field of Sports Sciences - ÖTKAN, Can Çavin; ULUN, Cihan; ÇOLAKOĞLU, Tekin (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
The aim of this study was to examine the information sharing levels of academicians working in the field of sports sciences in terms of various variables. A total of 279 academicians, 212 male (76%) and 67 female (24%), working in the field of sports sciences voluntarily participated in the study. The average age of the participants was determined as X̄year= 38.83 ± 8.85. The "Personal Information Form" created by the researcher and the "Information Sharing Scale" developed by Öneren, Çiftçi and Harman (2016) were used as data collection tools in the study. Before proceeding to the analysis process, it was tested whether the data provided the assumption of normality or not and it was seen that it was suitable for parametric tests. In this context, independent samples t-test and one-way anova were used in data analysis. It was determined that there is a significant difference between the inter-employee, individual and institutional information sharing sub-dimensions of the information sharing scale in terms of gender and the departments they work in only the institutional information sharing sub-dimension (p <.05). As a result, although the level of information sharing in the research group produced institutionally meaningful results, it was seen that the overall study was not sufficient and meaningful. Therefore, with this study, it was emphasized the need to review and strengthen the information sharing patterns and practices that are thought to affect the organizational effectiveness and efficiency of higher education institutions that undertake the mission of producing and sharing information in the field of sports sciences.